The talking T. Rex - Roy, Ron; Gurney, John Steven, Ill. (Scholastic, 2003)
Friends Dink, Josh and Ruth Rose try to track down the money that goes missing from a dinosaur museum fundraiser.
Gr.2-4
490
Keywords: Mystery fiction